Evaluating Teaching Efficiency among Filipino Teacher Interns: Insights for Enhancing Teacher Preparation and Advancing SDG 4 on Quality Education - Adigue, Andrea P. (Future Science / FSH-PH Publications, 2025)
This study assesses the teaching effectiveness of Filipino teacher interns in post-pandemic classrooms, focusing on instructional strategies, student–teacher interactions, and pedagogical efficacy. Employing a quantitative design with supplementary qualitative validation, data were collected from 24 teacher interns, 24 cooperating teachers, and 240 students in selected secondary schools under the supervision of DepEd Cabanatuan and DepED Nueva Ecija. Standardized rating scales, structured interviews, and classroom observations were used to assess communication proficiency, content knowledge, instructional material preparation, assessment design, and teaching strategies. Findings revealed high teaching efficiency, especially in differentiated instruction, digital tool integration, and strong communication skills. However, gaps in adaptability and instructional alignment emerged, as cooperating teachers’ ratings were slightly lower than the interns' self-evaluations. These results underscore the importance of ongoing professional development to enhance adaptive teaching and reflective self-evaluation, thereby aligning stakeholder expectations and advancing Sustainable Development Goal 4 (Quality Education).